Gap Arthroplasty With Temporalis Fascia Interposition For The Treatment Of Temporomandibular Joint Ankylosis: Case Report - Paula Perrotta dos Reis Santos; Rodrigo Figueiredo de Brito Resende; Antônio Marcos Pantoja de Azevedo; Bruno Turéli; Guilherme Pivatto Louzada (Portal de Periódicos da Marinha do Brasil, 2023)
Ankylosis of the temporomandibular joint (TMJ) is characterized by the intracapsular union of the condyle-disc complex to the surface of the temporal bone, which can cause restriction of the mandibular movements and a limitation of a mouth opening. Alterations are also described as a restriction of masticatory capacity, difficulty in phonation and suitable oral hygiene, as well as difficulty in social interaction. A 27-year-old female patient with a bilateral history of parasymphysis and mandibular condyle fracture after a trauma in 2014, which evolved to an ankylosis of the right TMJ, with a maximum mouth opening of 13.27 mm. For the treatment of the described case, it was used the Al-Kayat approach, ipsilateral coronoidectomy and resection of the ankylotic mass in gap with interposition of temporalis muscle fascia flap on the right side. After six months of the surgical procedure, it was made a new computed tomography of the face in which it was possible to notice the absence of lesions and signs of recurrence of the ankylosis. It was also observed the maintenance of the gap space made by the bone resection. The satisfactory result of the technique was attributed to the achievement and stabilization of an adequate mouth opening, improved chewing ability and phonation. Besides the clinical success, an advantage of the technique used was the low cost of the procedure by using only temporal muscle interposition without the use of alloplastic materials. In addition, the associated ipsilateral coronoidectomy was sufficient to help maintaining the achieved mouth opening, and the contralateral coronoidectomy was not necessary, as a result it was minimized the surgical time and morbidity of one more accessed surgical site.